Hybrid Nanosystems of Antibiotics with Metal Nanoparticles—Novel Antibacterial Agents - Tatyana I. Shabatina; Olga I. Vernaya; Mikhail Y. Melnikov (Molecules, 2023)
The appearance and increasing number of microorganisms resistant to the action of antibiotics is one of the global problems of the 21st century. Already, the duration of therapeutic treatment and mortality from infectious diseases caused by pathogenic microorganisms have increased significantly over the last few decades. Nanoscale inorganic materials (metals and metal oxides) with antimicrobial potential are a promising solution to this problem. Here we discuss possible mechanisms of pathogenic microorganisms’ resistance to antibiotics, proposed mechanisms of action of inorganic nanoparticles on bacterial cells, and the possibilities and benefits of their combined use with antibacterial drugs. The prospects of using metal and metal oxide nanoparticles as carriers in targeted delivery systems for antibacterial compositions are also discussed.